2018
DOI: 10.1007/s12178-018-9461-8
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Degenerative Rotator Cuff Tears

Abstract: Purpose of Review In the past several years, there have been significant advances in our understanding of the natural history of rotator cuff disease. Studies have continued to provide valuable insight into the clinical, radiographic, and anatomic features of these atraumatic tears. Our purpose is to summarize the findings and contributions from these recent high-quality studies. Recent Findings Current research has continued to describe and provide understanding into the natural history of atraumatic rotator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 39 publications
1
34
0
3
Order By: Relevance
“…Although the exact pathogenesis of RC tendinopathy is still under debate [ 5 , 7 ], it is thought to be a multifactorial disease [ 3 ], with several cofactors that contribute to weaken tendons until their rupture. Previous studies have indicated that repetitive motion disorders occur mainly in women [ 14 ] and in advanced age [ 5 , 6 ]. It may imply a potential role of postmenopausal hormonal modifications in influencing the natural history of these ailments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the exact pathogenesis of RC tendinopathy is still under debate [ 5 , 7 ], it is thought to be a multifactorial disease [ 3 ], with several cofactors that contribute to weaken tendons until their rupture. Previous studies have indicated that repetitive motion disorders occur mainly in women [ 14 ] and in advanced age [ 5 , 6 ]. It may imply a potential role of postmenopausal hormonal modifications in influencing the natural history of these ailments.…”
Section: Discussionmentioning
confidence: 99%
“…In the USA, each year approximately 4.5 millions of people suffer from shoulder pain and the majority of them are due to RC tears [ 3 , 4 ]. The prevalence of the disease increases with age, affecting up to 67% of patients over 80 years [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Do they behave different from conservatively treated full-thickness rotator cuff tears on natural history, which progress (and become symptomatic) over time? [8][9][10] Or are these more sustainable? In a systematic review (N ¼ 643) presented by Malahias et al, 11 all mean postoperative clinical and functional subjective scores, as well as the muscle strength of patients treated with arthroscopic partial repair, were significantly improved compared with the mean preoperative values.…”
Section: See Related Article On Page 2080mentioning
confidence: 99%
“…Rotator cuff tear (RCT) is a representative muscletendinous disease-causing shoulder pain (1), and recently, its prevalence rate is remarkably increasing by an aging population and various sports activities (2,3). For RCTs, surgical repair is prevalent and has been a commonly accepted treatment, especially when the conservative management was failed (4).…”
mentioning
confidence: 99%